The Complexities Associated with Caring for Hospitalised Infants with Neonatal Abstinence Syndrome: The Perspectives of Nurses and Midwives - Jaylene Shannon; Stacy Blythe; Kath Peters (MDPI AG, 2021)
The global incidence of Neonatal Abstinence Syndrome (NAS) has increased significantly in the last decade. Symptoms of NAS manifest from the central and autonomic nervous systems as well as the gastrointestinal system and vary in severity and duration. The clinical management of infants experiencing NAS is dependent on symptoms and may include both pharmacological and non-pharmacological measures. In cases where symptoms are severe, infants may be admitted to special care nurseries or neonatal intensive care units. Existing research on nurses' involvement in caring for infants with NAS focuses on pharmacological and non-pharmacological interventions to treat physical symptoms associated with NAS. This research sought to add to the body of knowledge around NAS and conveys nurses' and midwives' experiences of delivering care for infants with NAS. Semi-structured interviews were held with nine nurses/midwives. Interviews were audio-recorded, transcribed verbatim and thematically analysed. Five themes emerged from the data. These themes are: Complex care needs; Prioritising physiological care; Experiencing compassion fatigue; Lacking continuity of care; and Stigma. The findings demonstrated the complex nature of care provision for infants with NAS. Competing priorities and the stigmatising nature of NAS threaten optimal care being delivered to these vulnerable infants and their parents.